Monitoring of Aspirin (ASA) Pharmacodynamics with the Platelet Function Analyzer PFA-100® - Homoncik, Monika; Jilma, Bernd; Hergovich, Nicole; Stohlawetz, Petra; Panzer, Simon; Speiser, Wolfgang (Thrombosis and Haemostasis, 2000)
Anti-platelet drug therapy is currently performed without monitoring, because the established method of platelet aggregometry is cumbersome. The recently developed platelet function analyzer PFA-100® measures shear stress dependent, collagen epinephrine (CEPI) and collagen adenosine diphosphate (CADP) induced platelet plug formation. As the PFA-100 provides a valuable tool to detect patients with platelet dysfunction more efficiently and cost-effectively than aggregometry, we investigated its potential to monitor the efficacy of aspirin treatment.All healthy volunteers (n = 10) received a fractionated infusion of L-aspirin to establish individual dose-response curves. Further, in a randomized, double-blind, placebo controlled two-way cross over study the same volunteers received either 50 or 100 mg aspirin/day p.o. for a period of 11 days to determine the day-to-day variability CEPI induced closure time (CT) under constant intake of low dose aspirin, and to compare the efficacy of those two doses.Intra- and intersubject variability of CEPI-CT averaged 9% and 22%, respectively. Seven volunteers exceeded the maximum of CEPI-CT (>300 s) already after infusion of 100 mg L-aspirin. Intake of 100 mg of aspirin elicited a more rapid onset of effect than 50 mg, which was only significant on days 3 and 4 of aspirin intake. The aspirin induced CEPI-CT prolongation correlated positively with basal CEPI-CT values (r = 0.86; p = 0.001) and were strongly dependent on von Willebrand Factor levels (r = -0.9; p = 0.001).Thus, the PFA-100 system appears suitable to demonstrate an aspirin-induced platelet effect in a longitudinal study, and may be adequate to monitor a patient’s compliance. However, prospective trials have to be conducted to demonstrate whether the EPI-CT achieved under ASA-intake has predictive value for cardiovascular outcome.
Keywords: Aspirin; platelet function analyzer; PFA-100; alpha2-integrin